2015
DOI: 10.1007/s10461-014-0981-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Number of Sex Workers in South Africa: Rapid Population Size Estimation

Abstract: Although recognized as a vulnerable population, there is no national population size estimate for sex workers in South Africa. A rapid sex worker enumeration exercise was undertaken in twelve locations across the country based on principles of participatory mapping and Wisdom of the Crowd. Sites with a range of characteristics were selected, focusing on level of urbanisation, trucking, mining and borders. At each site, sex worker focus groups mapped local hotspots. Interviews with sex workers at identified hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 11 publications
3
45
3
Order By: Relevance
“…The estimates derived from our methodology in these cities are largely consistent with 2013 estimates by Konstant et al, derived from different methodologies [7]. While stakeholders acknowledged the PSE's appeared to be lower than they had expected (a result also reported by Konstant et al 2013), stakeholders were persuaded to rely on these results as they were based upon empirical methodologies that were consistently, transparently applied to the IBBS PSE data.…”
Section: Comparison With Prior Worksupporting
confidence: 84%
See 1 more Smart Citation
“…The estimates derived from our methodology in these cities are largely consistent with 2013 estimates by Konstant et al, derived from different methodologies [7]. While stakeholders acknowledged the PSE's appeared to be lower than they had expected (a result also reported by Konstant et al 2013), stakeholders were persuaded to rely on these results as they were based upon empirical methodologies that were consistently, transparently applied to the IBBS PSE data.…”
Section: Comparison With Prior Worksupporting
confidence: 84%
“…Studies conducted in the 1990s and 2000s observed that as many as half of all sex workers sampled were HIV-positive but did not include PSEs [5,6]; recent South African initiatives aimed to meet the HIV needs of key populations, including those sponsored by the US President's Emergency Plan for AIDS Relief (PEPFAR) and The Global Fund to Fight AIDS, Tuberculosis and Malaria (the Global Fund), have highlighted the need for reliable, methodologically rigorous PSEs for key populations generally and FSW in particular. In 2013, fieldwork undertaken by the South African National AIDS Council (SANAC) and sponsored by the Global Fund estimated that there were roughly 150,000 FSW in South Africa, or nearly 1% of the adult female population aged 15-49 years [7]. Despite the explicit inclusion of FSW in South Africa's national HIV strategic plans since at least 2007, prior to 2016 these efforts had not been informed by rigorously collected surveillance or survey data to quantify HIV treatment or biomedical prevention for the FSW population.…”
Section: Introductionmentioning
confidence: 99%
“…[3135] By insisting on safe sex, FSWs risked physical and sexual abuse from clients and loss of possible income, a pattern well demonstrated in the literature. [7,22,3638] The prospect of receiving more money and avoiding violence creates pressure that incentivizes FSWs engagement in risky sex. [11,19,21,36,38,39] A study by Malta et al [40], conducted in Brazil showed that in moments of pressure and uncertainty, FSWs relied on physical assessments to determine HIV serostatus, despite high levels of HIV knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Some clients did not carry condoms, and at times threatened violence if FSWs insisted on condom use, as found in other studies. [57,22,33,39,40] LDTDs are known to have high HIV rates, largely due to irregular condom use with FSWs. [21,22,40] As seen in other studies some LDTDs are more likely to report condom use with a one-night stand as opposed to regular FSWs with whom they have an attachment.…”
Section: Discussionmentioning
confidence: 99%
“…We compared recommended proportions to the 2011 census-derived adult population of females (FSW) and males (MSM) aged 15-49 (the approved protocol for each survey permitted inclusion of minors at least 16 years of age; for FSW, per protocol, individuals under age 18 underwent additional screening for evidence of trafficking and were referred to appropriate social services), based on the degree of urbanicity (large metropolitan municipalities versus smaller provincial district municipalities). For FSW, this range was 0.4-0.6% of females described by Konstant and colleagues;(29) for MSM, 1.2%-2.0% described by Caceres and colleagues. (30)…”
Section: Methodsmentioning
confidence: 82%